Characterisation of magnesium, zinc and iron sulfates for thermochemical storage. Issue 2 (10th December 2019) - Rehman, Ata Ur; Hayat, Asif; Munis, Adnan; Zhao, Tianyu; Israr, Muhammad; Zheng, Maosheng
Abstract : Thermochemical heat-storage materials such as magnesium, zinc and iron sulfates offer high energy-storage densities and a reliable means of long-term storage of solar energy. In this research study, the dynamic properties of these three salts were investigated based on their hydration and dehydration characteristics. To investigate the effect of regeneration temperatures on the physio-chemical properties of the materials, four sets of temperatures were used. At 100°C, zinc sulfate showed a significant loss of water as compared to magnesium and iron salts, while in the hydration process at lower temperatures, zinc sulfate showed the highest sorption enthalpy and energy density. Furthermore, the crystallinity of salt hydrates was characterised using powder X-ray diffraction measurements, which revealed that dehydration of water molecules occurred only in magnesium sulfate, whereas partial distortion occurred in iron sulfate with a rise in temperature. Collating the results together indicated that zinc sulfate is more energy efficient than both magnesium and iron sulfate. With a calculated hydration energy density at 100°C of 1·26 GJ/m 3, zinc sulfate is the best option among the three salts for its use as a thermochemical material.